Орфографический словарь - Курганова Н.В. (Детский иллюстрированный словарь, 2009)
Экземпляры: (12112009) / Инвентарный номер: 45147 / Цена: 181.40 / Сис.шифр: 81.2Рус-4 мл. 45147 / Авт.знак: О-70 / ББК: 81.2Рус-4 мл.